Can illegitimate job tasks be reduced by a participatory organizational-level workplace intervention? Results of a cluster randomized controlled trial in Danish pre-schools - Elisabeth Framke; Ole Henning Sørensen; Jacob Pedersen; Reiner Rugulies (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: We examined whether a cluster randomized controlled participatory organizational-level workplace intervention affected the level of unnecessary, unreasonable, and illegitimate tasks. METHODS: A cluster randomized controlled trial was implemented in municipal pre-schools. The intervention used a participatory approach and aimed improving the psychosocial working environment by focusing on core tasks. The sample consisted of 41 pre-schools with 404 employees in the intervention group and 30 pre-schools with 230 employees in the control group. We measured unnecessary and unreasonable tasks at baseline and at two-year follow-up by one item on unnecessary and one item on unreasonable tasks, respectively, and combined both items into a measure of illegitimate tasks. We analyzed within- and between-groups changes in unnecessary and unreasonable tasks and in the combined measure of illegitimate tasks. RESULTS: The scores for unnecessary, unreasonable, and illegitimate tasks remained virtually unchanged in the intervention group and increased in the control group. The different development in the two groups was statistically significant for unreasonable tasks (+0.02 versus +0.13, P=0.04) and the combined measure of illegitimate tasks (+0.01 versus +0.11, P=0.04) but not for unnecessary tasks (+0.00 versus +0.08, P=0.16). CONCLUSION: A comprehensive participatory organizational-level intervention with a focus on core job tasks may protect against an increase in illegitimate tasks in Danish pre-schools.